ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK DAERAH DI KABUPATEN MANOKWARI TAHUN 2013 – 2017 - Stenly Andry Ririhena; Marcus R. Maspaitella; Rumas Alma Yap (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
This study aims to determine the influence and the most dominant factors affecting tax revenue in Manokwari Regency in 2013-2017. This study uses quantitative methods. The type of data used is secondary data consisting of local tax revenues, number of visitors to tourism objects, hotel room occupancy rates and GDP at constant prices in Manokwari Regency. The data collection method uses the library method, while the analytical tool used is the multiple linear regression analysis method. The results showed that partially income per capita had a positive and significant effect on tax revenue in Manokwari Regency, the number of visitors to tourism objects had a negative and significant effect on tax revenue in Manokwari Regency and hotel room occupancy rates had a positive and significant effect on local tax revenue in Manokwari Regency. . The dominant factors on local tax revenue are income per capita and hotel room occupancy which have a positive and significant effect on local tax revenue in Manokwari Regency.